Arica y Parinacota, a south andean cultural landscape of universal significance - Guillén Cárdenas, Ángel (2016)
The current trends in the 15th region show an ostensible demographic decline of rural areas and a disproportionate urbanization of the coast in detriment of the rural, Aymara and Andean areas.The activation of the Cultural Landscape of Arica and Parinacota project, sponsored by the Regional Government within the PPVP of SUBDERE and promoted by Altiplano Foundation, is an alternative for territorial development in northern Chile.The appreciation as well as the recognition of Arica and Parinacota as the first Andean Cultural Landscape of Chile is an important goal that will boost regional development. The conceptual, methodological and operational structure of the region as a Cultural Landscape could result in several benefits: enhance its innovative image, improve the relationship with the ancestral heritage, integrate the Aymara and Andean communities, generate a visionary culture of the territory, link the territory to sustainability, articulate identity values, add to the public policy, and strengthen the use of various projective scales.